Macro-Regional Disparities in Specialized Dental Care for Children in the Brazilian Unified Health System: An Ecological Study - Ricardo Barbosa Lima; Ana Paula Gomes e Moura; Débora Amorim Alves de Aguiar; Paulo Nelson-Filho; Léa Assed Bezerra da Silva; Raquel Assed Bezerra da Silva (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate macro-regional disparities in specialized outpatient dental care for children in the Brazilian Unified Health System (SUS). Material and Methods: An ecological study was conducted using a longitudinal, retrospective, and quantitative approach. The number of outpatient dental procedures (ODPs) performed by Pediatric Dentists in the SUS was retrieved by the Outpatient Information System (SIA/SUS), considering the period between 2008 and 2022, as well as the five macro-regions of Brazil. Statistical analysis was based on descriptive and analytical approaches. The significance level was adjusted to 5%. Results: More than 29 million outpatient dental procedures were performed in the last 15 years by Pediatric Dentists in the SUS. The incidence rate of ODPs was significantly lower in the Northeast macro-region compared to the other macro-regions and the national estimate (p<0.05). The north was the only macro-region that showed a decreasing temporal trend over the last 15 years (p=0.026), while the others were stationary (p>0.05). However, when the COVID-19 pandemic years were removed, testing from 2008 to 2019, the trend was also stationary (p=0.351). In addition, the North macro-region was the only one not correlated with the national estimate (p=0.478), showing a distinct pattern in the incidence rate of ODPs over the last 15 years. Nonetheless, The variability of this particular variable was striking across all macro-regions, but it was especially pronounced in the north. Conclusion: There are macro-regional disparities in specialized dental care for children in the Brazilian Unified Health System.